IMPLEMENTASI PROGRAM SMART FARMING MELALUI PENDAMPINGAN PEMBUATAN POC DAN APLIKASI DRONE SPRAYER DI DESA TELLE - Hasmi Hasmi; Rustan Rustan; Selvina Syahnur; Nur Faidah; Muh. Ridha Nugraha; Syahrullah Syahrullah (STAI Darul Qalam Tangerang, 2022)
Community service program (KKN) in Puangrimaggalatung University was held in Telle Village for 2 months from January 25, 2022 to March 28, 2022. The location for the Integrated Thematic Community Service Program is Telle Village, Ajangale Sub-district, Bone Regency, with a target of farming communities. Various KKN-Thematic work programs have been implemented. The KKN-Thematic activities that have been carried out began with land mapping, assistance in making POCs, demonstrations and implementation of drone sprayers, monitoring, evaluation and socialization of the results of drone sprayer demonstrations. The results achieved from the implementation of the Integrated Thematic Community Service Program are applying new technology in agriculture, training community skills in utilizing agricultural waste, increasing the knowledge of farming communities on agricultural technology used to prevent or minimize the impact of exposure to chemicals on health. The Integrated Thematic Community Service Program, apart from being a vehicle for assistance to the community, is also a way for Puangrimaggalatung University to contribute to implementing new innovations in the agricultural sector. The existence of the Integrated Thematic KKN students is expected to have a better influence and change on the community, especially regarding the safety of farmers in agricultural activities